A Generalized Integrated Corridor Diversion Control Model for Freeway Incident Management. (28th May 2013) - Liu, Yue; Li, Peng; Wehner, Kevin; Yu, Jie
Abstract This article presents a generalized diversion control model for freeway incident management that is capable of concurrently optimizing the detour rates and arterial signal timings over multiple roadway corridor segments between the freeway and its neighboring arterial. To capture various operational complexities due to the interactions between multiple diversions, this study has developed an extended corridor traffic flow model and integrated it in the overall optimization process. A biobjective control model is developed to maximize the utilization of available corridor capacity while not significantly increasing the total time spent by travelers on the detour route to ensure their compliance to the routing guidance. Genetic algorithm integrated with the rolling time horizon approach is employed to solve the proposed model. Case studies with a stretch of the I‐94 corridor westbound from downtown Milwaukee to Waukesha have demonstrated the potential of the developed model for use in nonrecurrent congestion management.